A Comparative Study of some Typical Sal Forest Soils of Doon Valley with Reference to their Organic Matter - singhal, R. M.; Pathak, T. C.; Banerjee, S. P. (Indian Forester, 1976)
A considerable difference in the nature or humus was observed in the two typical sal forest soils of Doon Valley. The humus of the soils obtained from Asarori is predominantly humic in nature with greater condensation of aromatic rings and thus more mature as compared to that of Jhajra which is more lignious and fulvic in nature, containing more of side chains. Greater hydrolysability, oxidisability and mobility of humus of Asarori have been responsible for better soil conditions from the point or view of site quality and also nutrient cycling.